Living adult education Freire in Scotland - Kirkwood, Gerri (International issues in adult education, 2011)
The Adult Learning Project in Edinburgh, affectionately known as ALP, is a sustained experiment in applying the principles of the Brazilian educator, Paulo Freire, in a European post-industrial urban environment. Because this book explains so sensitively the theory and rationale of Freirean education, and describes so carefully the Freirean process at work in a Scottish setting, it will hearten and inspire all those who fear the iron hold of mechanistic and passive approaches to learning. Lalage Bown From 1979 to 2011, ALP has written a new chapter in the history of popular education, locally and globally, honouring the brilliance of the onelie begetter of this approach, Paulo Freire, whose writings have inspired us all. Colin and Gerri Kirkwood The fundamental concern in all of Paulo Freire's work is to assert the possibility and potential of human agency, by challenging the passivity and fatalism of ordinary people, intervening purposefully in their lives and enabling them to lever themselves out of immersion in the culture of silence. Through its pedagogy and curriculum, ALP has made a significant contribution to enabling the often marginalized voices of Scottish communities to be heard. For educators the world over who share similar aims and values, the experience of ALP is insightful, instructive and inspirational. Jim Crowther and Ian Martin The period since 1990 has been momentous in the life of ALP, in the sense that ordinary people became involved in an extraordinary political process which changed the life of Scotland forever. Vernon Galloway, Stan Reeves and Nancy Somerville This book will be of interest to educationalists, social scientists and psychologists throughout the world, and in particular to practitioners, students, teachers and promoters of schooling, adult, further and higher education, community development, practical and liberation theology, health and wellbeing, and counseling and psychotherapy. - Publisher's description.